The role of host response to chemotherapy: resistance, metastasis and clinical implications: review - Deo, Abhilash; Sleeman, Jonathan P.; Shaked, Yuval (Clinical & experimental metastasis, 2023)
Chemotherapy remains the primary treatment for most metastatic cancers. However, the response to chemotherapy and targeted agents is often transient, and concurrent development of resistance is the primary impediment to effective cancer therapy. Strategies to overcome resistance to treatment have focused on cancer cell intrinsic factors and the tumor microenvironment (TME). Recent evidence indicates that systemic chemotherapy has a significant impact on the host that either facilitates tumor growth, allowing metastatic spread, or renders treatment ineffective. These host responses include the release of bone marrow-derived cells, activation of stromal cells in the TME, and induction of different molecular effectors. Here, we provide an overview of chemotherapy-induced systemic host responses that support tumor aggressiveness and metastasis, and which contribute to therapy resistance. Studying host responses to chemotherapy provides a solid basis for the development of adjuvant strategies to improve treatment outcomes and delay resistance to chemotherapy. This review discusses the emerging field of host response to cancer therapy, and its preclinical and potential clinical implications, explaining how under certain circumstances, these host effects contribute to metastasis and resistance to chemotherapy.